Halal Tourism: World Cup Qatar 2022 - Ma'wa, Muhamad Agus Futuhul; Babud, Syarifah Salsabila; Listiyah, Alimatul (Afkaruna: International Journal of Islamic Studies (AIJIS), 2023)
Halal tourism is said to be a new perception of tourism that provides the opportunity to travel in accordance with Islamic rules. The concepts formed and implemented in halal tourism do not violate Islamic principles. This research uses a qualitative approach by applying library research methods. The data used in this research is secondary data, namely books, literature, notes and reports and other appropriate sources (internet, newspapers, etc.) that are related to the problem being solved by determining the research topic. , conducting studies related to theories related to the research topic. Qatar, with Islam as the state religion and the majority of its population being Muslim, has become one of the Muslim-friendly tourist destinations. Although Qatar also has many communities of other religions, Islam greatly influences the lives and culture of Qatari people. The state guides the religious life of Muslims in Qatar through the Ministry of Awqaf and Islamic Affairs. Its vision is “to build a contemporary Islamic society by developing Sharia and cultural heritage”. Qatar will host the world cup in 2022 which will become the center for gathering football fans from all over the world where all aspects are of concern to stakeholders in all sectors, especially the tourism sector. Global Muslim Travel Index (GMTI) Determines the cumulative score based on the achievements of each tourist attraction or country providing halal tourism services. These four variables have varying weights which will change the values obtained. With a weight of 40%, services at tourism destinations have the greatest value. This means that when visitors are at a tourist location, sharia determines the continuity of the tourism.